STUDENTS"™ LEARNING ACTIVITIES IN PHYSICS CLASSES OF GRADE X BY IMPLEMENTING INQUIRY TRAINING MODEL - Sirait, Jeliana Veronika; Amnie, Erlida; Ekaputra, Firdiawan (Jurnal Pendidikan Matematika dan IPA, 2024)
This research aims to analyze students"™ learning activities in implementing the inquiry training learning model in grade X. The physics lesson material taken in this research is linear motion. SMAN Percut Sei Tuan is the location where the research was carried out. The samples in this study were two classes: grade X-9 which uses inquiry training model and X-5 which uses direct instruction model. The type of this research is quasi experiment. The observation sheet was used as an instrument in this research. The data in this research were analyzed using the independent sample t test to find out the differences in student learning activities using the inquiry training model and the direct instruction model. Student learning activities are observed during learning activities by an observer. The average of student learning activity in class X-9 is 80 and class X-5 is 71. Based on the results of data analysis, it was found that the sign value 0,05. So it can be concluded that there are differences in student learning activities using the inquiry training model and the direct instruction model.